ROLE, AUDIENCE, FORMAT, AND TOPIC (RAFT) STRATEGY TO ENHANCE EFL LEARNERS’ DESCRIPTIVE WRITING: A STUDY IN AN INDONESIAN MADRASAH - Patmala, Kiki; Hartina, St.; Wisran, Wisran (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2025)
Writing remains one of the most demanding skills for English as a Foreign Language (EFL) learners, particularly in producing descriptive texts that require lexical variety, grammatical accuracy, and mechanical precision. Traditional approaches in Indonesian classrooms often emphasize form-focused drills and teacher-centered instruction, which may limit students’ engagement and creativity. This study investigates the effectiveness of the Role–Audience–Format–Topic (RAFT) strategy in enhancing senior secondary students’ descriptive writing performance. A quasi-experimental design was employed with 48 twelfth-grade students from MA Batusitanduk, divided into an experimental group taught using RAFT (n = 24) and a control group taught through conventional methods (n = 24). Both groups completed a pre-test and post-test assessed on vocabulary, grammar, and mechanics using a validated analytic rubric. Results revealed that the experimental group achieved a significantly higher mean post-test score (M = 72.33) than the control group (M = 65.33), t(46) = -5.432, p < .001, with a large effect size (Cohen’s d = 1.52, 95% CI [8.32, 15.02]). These findings confirm that RAFT effectively scaffolds planning and audience awareness, leading to substantial improvement in descriptive writing. The study offers theoretical implications for integrating cognitive and genre-based pedagogy, and practical recommendations for EFL teachers seeking to promote meaningful and engaging writing instruction in secondary education.